Obraz głupca w rosyjskim socjolekcie młodzieżowym - Sadowska, Monika (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
Teenage sociolect very rapidly reacts to everything that is happening around us, and, consequently, gives an up-to-date view on the way of perceiving the world by a specific group of people using particular terminology. This paper is an attempt to briefly describe the development of teenage sociolect, which is a highly interesting language phenomenon ,and to systemize the sources of lexical units, which describe the person with intellectual deficits, as well as to depict the process of forming these units within lexical semantics.